Influence of oxidant passivation on controlling dishing in alkaline chemical mechanical planarization*Project supported by the Special Project Items No. 2 in National Long-Term Technology Development Plan, China (No. 2009ZX02308). (December 2015) - Jia 贾, Shaohua 少华; Liu 刘, Yuling 玉岭; Wang 王, Chenwei 辰伟; Yan 闫, Chenqi 辰奇
Abstract: The article studied the electrochemical behavior of P2 alkaline polishing slurry. The main research is the changing discipline of E corr and I corr in the Cu electrolyte at different concentrations of oxidant H2 O2 . It compares potentiodynamic polarization curves in different P2 slurries and analyzes the passivation function of H2 O2 acting on controlling dishing. The result implies that the potential increases gradually and then levels off while the current density on the contrary decreases with the augment of H2 O2 concentration. In addition, dishing declines with the increasing of H2 O2 along with the optimization of planarization of the alkaline P2 slurry.